2013
DOI: 10.1002/bies.201300132
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 5‐phosphate: A nuclear stress lipid and a tuner of membranes and cytoskeleton dynamics

Abstract: Phosphatidylinositol 5-phosphate (PtdIns5P), the least characterized among the three phosphatidylinositol monophosphates, is emerging as a bioactive lipid involved in the control of several cellular functions. Similar to PtdIns3P, it is present in low amounts in mammalian cells, and can be detected at the plasma membrane and endomembranes as well as in the nucleus. Changes in PtdIns5P levels are observed in mammalian cells following specific stimuli or stresses, and in human diseases. Recently, the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 104 publications
(185 reference statements)
0
39
0
1
Order By: Relevance
“…However, PI5P effectors outside the nucleus that might be involved in its function on membranes facing the cytosol are sparse. Very recently, our laboratory has shown that PI5P is able to activate the small GTPase Rac1, therefore regulating actin cytoskeleton dynamics and cell invasion (Viaud et al, 2014b). Our present work identifies TOM1, through its VHS domain, as a PI5P effector regulating endosomal maturation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, PI5P effectors outside the nucleus that might be involved in its function on membranes facing the cytosol are sparse. Very recently, our laboratory has shown that PI5P is able to activate the small GTPase Rac1, therefore regulating actin cytoskeleton dynamics and cell invasion (Viaud et al, 2014b). Our present work identifies TOM1, through its VHS domain, as a PI5P effector regulating endosomal maturation.…”
Section: Discussionmentioning
confidence: 55%
“…In the nucleus, in response to stress signaling (Jones et al, 2006), PI5P acts as a regulator of chromatin organization and gene expression though its interaction with the PHD (plant homeodomain) domaincontaining protein ING2 (Gozani et al, 2003). Outside the nucleus, PI5P has been shown to be implicated in the regulation of membrane dynamics and trafficking (Shisheva, 2013;Viaud et al, 2014a). In this context, three potential pathways lead to an increase in the amount of PI5P: one involves the direct phosphorylation of phosphatidylinositol by the 5-kinase PIKfyve, the second involves a PI3P-PI(3,5)P 2 -PI5P route with the concerted action of the PIKfyve and the 3-phosphatases of the myotubularin family (Viaud et al, 2014a) and the third uses PI(4,5)P 2 as a source of PI5P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he phosphatidylinositol 5-phosphate 4-kinases (PI5P4Ks) are an enigmatic family of three (PI5P4Kα, -β, and -γ) with cellular functions that remain poorly understood (1)(2)(3). In general, their principal activity is believed to be to remove and thus, regulate the levels of their substrate phosphatidylinositol 5-phosphate (PI5P).…”
mentioning
confidence: 99%
“…Le PtdIns5P est l'un des derniers PI à avoir été identifié [9]. Il est présent en faible quantité dans les cellules quiescentes.…”
Section: Ptdins5punclassified